Edukasi Pencegahan Stunting Menggunakan Smart Chart pada Keluarga 1000 HPK - Kadar Ramadhan; Christina Entoh; Nurfatimah Nurfatimah; Cintu Waisawati; Maria Mowemba; Astiyani A. Laiga; Priska Anakoda (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
A mother's good knowledge about stunting is very important in preventing stunting in children. If a mother has enough knowledge about good nutrition, she can make the right decisions about the food to give to the child during the growth period, so that the child can grow well and avoid stunting problems. The goal of this activity is to increase the family's knowledge about stunting using a smart chart. This activity is carried out in Sangginora Village, Poso District, targeting families with children aged 0-23 months. The education media used is a smart chart containing 3 key messages: understanding, danger, and prevention of stunting. The results of the activity showed an increase in the mother's knowledge about stunting. The smart posters placed in the target houses allow for frequent reading by the mother and other family members. We recommend that the Family Support Team (TPK) of Sangginora Village attach the smart posters to new families in the First 1000 Days of Life (HPK).